Experimental determination of force acting on a sandwich conveyor's pressure roller in transport of bulk materials for the needs of failure analysis. (October 2022) - Hrabovsky, Leopold; Molnar, Vieroslav; Fedorko, Gabriel; Tkac, Jozef; Frydrysek, Karel
Highlights: Measurement proposal to identify failure condition. Measuring device design. Measurement of pressing force magnitude in various rollers arrangement. Experimental determination of force acting on pressure roller. Abstract: Sandwich conveyors are among continuous transport systems used to transport bulk materials over short distances. The principle of their operation deploys the one of classic belt conveyors. However, in contrast to them, they use two parallel conveyor belts, between which the bulk material is transported. The conveyor belts are pressed against transported material by pressure rollers. As a result of mutual interaction, forces emerge which make transport of bulk material possible at angles that conventional belt conveyors cannot handle. The magnitude and effect of these forces are most pronounced at the points of conveyor belt's contact with pressure rollers. However, in case of insufficient pressure, the transport process fails, and the conveyor is unable to perform its function. Through experimental measurements, it was found that the pressing force magnitude is about 20.8% smaller compared to the opposite arrangement and a roller spacing of 330 mm, and by 13.4% with a roller spacing of 660 mm. The aim of the paper is to design a measurement system and identify the magnitude of forces, using experimental measurements, based on which regression models can be determined and used in failure analysis. The paper presents results that can be applied in online monitoring of this type of transport for the needs of failure analysis, prediction, and operational indicator's assessment. Thus, preconditions are created to include such a type of transport system among the ones meeting Industry 4.0 criteria in the field of failure analysis.